An experimental study on a novel direct expansion based temperature and humidity independent control air conditioning system. (February 2019) - Chen, Wenjing; Fang, Guanyu; Wang, Caixia; Weng, Wenbing; Chan, Ming-yin; Deng, Shiming; Liu, Xuefeng; Yan, Huaxia
Abstract: Direct expansion (DX) air conditioning (A/C) system are widely used in various buildings because they are simpler and more energy efficient, and generally cost less to own and maintain. However, it is often problematical for a conventional On-Off controlled DX A/C system to simultaneously control indoor temperature and humidity, since the cooling and dehumidification process of air are highly coupled, unless costly extra equipment or complicated control method to decouple the cooling and dehumidification are provided. Therefore, a novel DX based temperature and humidity independent control air conditioning (DX-THIC) system with two parallel-connected condensers and two electronic expansion valves is presented for improved indoor environmental control and energy efficiency. This paper reports on an experimental study on the operating performances of a prototype experimental DX-THIC system. The experimental results demonstrated that the proposed DX-THIC system can provide independent control of indoor temperature and humidity. The experimental results also demonstrated that the indoor air humidity could influence the operating performances of the DX-THIC system.